Implementation of a course-based undergraduate research experience into an undergraduate immunology course - Gibbons Johnson, Rachel M. (Frontiers in Education, 2025)
Course-Based Undergraduate Research Experiences (CUREs) are a widely used pedagogical tool that effectively engage students in the process of doing science, leading to increased retention and student success in STEM. I have designed a CURE in which students in my upper-level immunology course investigate the immunomodulatory properties of herbal supplements. Students work collaboratively in a group to develop a hypothesis based on data from primary literature, design an experiment to test their hypothesis, collect and analyze data, and present their findings to their peers. By participating in this CURE, students gain valuable research experience and develop several “Key Competencies” that align with the Immunology Learning Framework.